Палімпсест як метафора пам’яті кул ьтури: своєрідність візуалізації - Пушонкова О. А. (Hileya: Scientific Bulletin / Gileya, 2018)
An analysis of the phenomenon of palimpsest as a metaphor for cultural memory is being carried out, which is caused by the change of its architectonic model in the culture of the XX - early. XXI century and enables the interpretation of culture as a dynamic text with firsthand, «source code», which is actualized in the context of the archaising processes as a «recall» of the first text. The features of visualization in art, in particular in cinema and painting, present the phenomenon of a broken perspective and a cinematic canvas; flicker of archetypal horizon, polylinearity of time: reverse movement, complexity, confusion, absence. In the cultural-traumatic discourse, traumatic fixation leads to the «obliviondisplacement » of the past, embodied in the meaningless principle of the collage, with its tautological procedural and images of «fragments», «debris», «rubbish» and «rubbish». Forgetting makes life possible «here and now», but challenges the historical dimensions of memory and its collective background, which leads to the phantomization of the past and the formation of its hybrid simulations. The visualization of the traumatic experience forms the «islets of the confusion of passion» and forms the «range of blindness» in the culture of total visualization.